Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.11622/smedj.2017059
|View full text |Cite
|
Sign up to set email alerts
|

The role of dispatch in resuscitation

Abstract: The role of the dispatch centre has increasingly become a focus of attention in cardiac arrest resuscitation.The dispatch centre is part of the fi rst link in the chain of survival because without the initiation of early access, the rest of the chain is irrelevant. The infl uence of dispatch can also extend to the initiation of bystander cardiopulmonary resuscitation, early defi brillation and the rapid dispatch of emergency ambulances. The new International Liaison Committee on Resuscitation, the American Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
(21 reference statements)
0
16
0
6
Order By: Relevance
“…(8,9) Although the rate of bystander CPR in Singapore remained at a low of about 20% until 2011, the implementation of dispatcher-assisted CPR by the Singapore Civil Defence Force has led to a rise in bystander CPR rates, to 49% in 2015. (10)(11)(12) Thus, dispatcher-assisted CPR may improve outcomes in patients with out-of-hospital cardiac arrest in Singapore. (13) One possible reason that laypersons may be averse to performing bystander CPR is that mouth-to-mouth ventilation is still included in the standard Basic Cardiac Life Support (BCLS) protocol, although evidence suggests that it does little to improve outcomes.…”
Section: A 6bmentioning
confidence: 99%
See 1 more Smart Citation
“…(8,9) Although the rate of bystander CPR in Singapore remained at a low of about 20% until 2011, the implementation of dispatcher-assisted CPR by the Singapore Civil Defence Force has led to a rise in bystander CPR rates, to 49% in 2015. (10)(11)(12) Thus, dispatcher-assisted CPR may improve outcomes in patients with out-of-hospital cardiac arrest in Singapore. (13) One possible reason that laypersons may be averse to performing bystander CPR is that mouth-to-mouth ventilation is still included in the standard Basic Cardiac Life Support (BCLS) protocol, although evidence suggests that it does little to improve outcomes.…”
Section: A 6bmentioning
confidence: 99%
“…This would translate to improved outcomes for patients suffering from out-of-hospital cardiac arrest in Singapore. (11)(12)(13)(14)16) While 82.6% and 57.2% of Singaporeans feel that all adults should be trained in CPR and AED, respectively, the actual proportion of Singaporeans who are trained in these is only 34.3% and 31.4%, respectively. (17) In order to enhance training in CPR and AED, the National Resuscitation Council has set up a system for monitoring and maintaining standards of life support training, leading to a large increase in the number of training centres for BCLS.…”
Section: A 6bmentioning
confidence: 99%
“…(1) Od instrukcija koje dispečer daje preko telefona zavisi i sam kvalitet pruženih mera resuscitacije, kompresija grudnog koša i ventilacija (2). U mnogim zemljama se sprovode edukacije dispečera o načinu komunikacije, prepoznavanju srčanog zastoja ako i navođenju laika ka primeni mera KPR (3,4). Na ovaj način treninzi dispečera uz programe edukacije stanovnika o primeni KPR dodatno utiču na postizanje bolje saradnje a samim tim i ishoda postupka resuscitacije (5).…”
Section: Diskusijaunclassified
“…It is noteworthy that bystander CPR rates started increasing from early 2011, in conjunction with the launch of National Life Saving Day. Ng et al reported in their article (19) that by the end of 2015, the local bystander CPR rate had reached 49%, of which only 8% was owing to dispatcher-assisted CPR. The remainder of the increase, from 22% to 41% (almost doubling), was attributed to public, bystander-initiated CPR.…”
Section: National Life Saving Daymentioning
confidence: 99%